The Effect of Incentives and Work Stress on Employee Performance During the Covid-19 Pandemic in PTPN IV Kebon Tanah Raja - Fajar Rezeki Ananda Lubis (Institute of Computer Science (IOCS), 2021)
The purpose of this study is to determine the effect of incentives and work stress on employee performance during the COVID-19 pandemic.The present study was carried out in PTPN IV KEBON TANAH RAJA. The sample in this study consisted of 51 employees.Data was collected using a questionnaire in accordance with the indicators of each variable used. The data obtained were then analyzed using multiple linear regression analysis.The results show that incentives and work stress simultaneously have a significant effect on employee performance during the COVID-19 pandemic.The results of the t-test indicate that incentives and job stress have a significant effect on employee performance. The incentive factor has a more dominant effect on employee performance compared to job stress.